THE REPRESENTATION OF CHILD CHARACTERS IN MOVIES DEPICTING THE UNREST OF THE SOCIETY - Jha, Pragya; E S Latha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper examines the multifaceted representation of children in cinema. It explores how children are portrayed not merely as passive figures but as active agents within narratives, often reflecting societal values, anxieties, and changing perceptions of humanity. The analysis considers the various tropes and archetypes associated with child characters, such as the innocent, the precocious, the troubled, and the magician, and how these representations intersect with themes of family, identity, and the situations in which they thrive. Furthermore, it investigates the evolution of child representation across different historical periods, highlighting how cinematic portrayals of children shape and are shaped by cultural contexts.